2008
DOI: 10.1542/peds.2008-2171
|View full text |Cite
|
Sign up to set email alerts
|

Medical Emergencies Occurring at School

Abstract: Children and adults might experience medical emergency situations because of injuries, complications of chronic health conditions, or unexpected major illnesses that occur in schools. In February 2001, the American Academy of Pediatrics issued a policy statement titled "Guidelines for Emergency Medical Care in Schools" (available at: http://aappolicy.aappublications.org/cgi/content/full/pediatrics;107/2/435). Since the release of that statement, the spectrum of potential individual student emergencies has chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Statistics South Africa reported injury as the fourth leading cause of death in the 0-14 year age group, 10-25% of which occurred at schools [10]. A similar study in the USA identified injuries as the leading cause of death and disability among children, with 70% of injury-related deaths occurring in school children aged between 5-19 years [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistics South Africa reported injury as the fourth leading cause of death in the 0-14 year age group, 10-25% of which occurred at schools [10]. A similar study in the USA identified injuries as the leading cause of death and disability among children, with 70% of injury-related deaths occurring in school children aged between 5-19 years [1].…”
Section: Discussionmentioning
confidence: 99%
“…Children spend a considerable amount of time on the school premises away from their parents and guardians. For these learners, the school is a 'home away from home' and is supposed to be a 'safe haven' that offers them the needed healthy environment to learn, play and interact with fellow learners [1]. Despite precautionary measures, medical emergencies may occur unexpectedly.…”
mentioning
confidence: 99%
“… 3 According to the American Academy of Pediatrics, 10–25% of the United States (US) children’s accidents occur during school hours. 4 , 5 Research has identified three main areas related to first-aid injuries at school: (1) health problems and accidents; (2) teachers’ knowledge of first aid; and (3) the benefits of first-aid training programs for school staff. School students’ health problems include epileptic seizures, 6 diabetes, asthma attacks, sudden cardiac death, 7 , 8 dental trauma, 9–11 leg injuries, and nosebleeds.…”
Section: Introductionmentioning
confidence: 99%
“…5 In addition, the Sideline Preparedness Collaboration (comprised of six major professional organizations: American Academy of Family Physicians, American Academy of Orthopaedic Surgeons, American College of Sports Medicine, American Medical Society for Sports Medicine, American Orthopaedic Society for Sports Medicine, American Osteopathic Academy of Sports Medicine), American Academy of Pediatrics, and American Heart Association all endorse the formation and implementation of emergency plans in schools. 7 – 9 …”
Section: Introductionmentioning
confidence: 99%